2021
DOI: 10.1016/j.cell.2021.02.018
|View full text |Cite
|
Sign up to set email alerts
|

Time-resolved systems immunology reveals a late juncture linked to fatal COVID-19

Abstract: COVID-19 exhibits extensive patient-to-patient heterogeneity. To link immune response variation to disease severity and outcome over time, we longitudinally assessed circulating proteins as well as 188 surface protein markers, transcriptome, and T-cell receptor sequence simultaneously in single peripheral immune cells from COVID-19 patients. Conditional-independence network analysis revealed primary correlates of disease severity, including gene expression signatures of apoptosis in plasmacytoid dendritic cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

33
272
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 199 publications
(306 citation statements)
references
References 141 publications
(190 reference statements)
33
272
0
1
Order By: Relevance
“…This agrees with reports in which innate cytokine/chemokine signatures of immunopathology [7] have been associated with end-stage COVID-19 disease [16]. The lack of temporal coordination between innate and adaptive responses allows the persistence of a high viral load, which can trigger a second wave of inflammation, occurring during the third week from infection, which is crucial for the worst clinical outcomes [8].Pre-existing immunity to the virus in unexposed individuals.SARS-CoV-2-specific T cells have been detected in about 50% of unexposed individuals, suggesting T cell cross-reactivity between SARS-CoV-2 and common cold coronaviruses (CCC), which affect >75% of general young population [17]. High level of pre-existing memory CD4+ and CD8+ T cells could allow to favor a faster and stronger adaptive immune response upon exposure to SARS-CoV-2, limiting disease severity.…”
supporting
confidence: 88%
See 2 more Smart Citations
“…This agrees with reports in which innate cytokine/chemokine signatures of immunopathology [7] have been associated with end-stage COVID-19 disease [16]. The lack of temporal coordination between innate and adaptive responses allows the persistence of a high viral load, which can trigger a second wave of inflammation, occurring during the third week from infection, which is crucial for the worst clinical outcomes [8].Pre-existing immunity to the virus in unexposed individuals.SARS-CoV-2-specific T cells have been detected in about 50% of unexposed individuals, suggesting T cell cross-reactivity between SARS-CoV-2 and common cold coronaviruses (CCC), which affect >75% of general young population [17]. High level of pre-existing memory CD4+ and CD8+ T cells could allow to favor a faster and stronger adaptive immune response upon exposure to SARS-CoV-2, limiting disease severity.…”
supporting
confidence: 88%
“…to recruitment into tissues and apoptosis and their number is negatively related to disease severity [7]. Low numbers of pDCs can be responsible for the reduced presentation of viral epitopes to T cells and for defective activation of natural killer (NK) cells [8]. NK cells may be impaired early due to: i. the over production of cytokines (mainly IL-6) by infected APC [9], ii.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A longitudinal study of CD8 + T cells during SARS-CoV-2 infections revealed an exhausted phenotype of CD8 + T cells, based on the presence of exhaustion markers including PD-1, CTLA-4, and TIGIT, which, together with reduced poly-functionality according to markers such as IFN-γ, TNF-α, and IL-2 predicted disease severity [396]. However, other studies showed that CD8 + T cells are not exhausted but remain functional [397,398] and a significant proportion of SARS-CoV-2 reactive T cells with "exhausted" phenotype are also found in patients with mild COVID-19 [399]. Interestingly these cells exhibited lesser cytotoxic and inflammatory features and could maintain their exhausted state even after viral clearance.…”
Section: The Time Course Of T Cell Responses In Sars-cov-2 and Hiv-1 Infectionmentioning
confidence: 99%
“…Among the heavily distorted innate immune response typical of COVID-19, the latewave inflammatory response in particular is linked to COVID-19 disease severity [398,456,457]. The major differences in immune phenotype between moderate and severe cases are apparent after day 10 of infection.…”
Section: Cytokines and Innate Immune Responsementioning
confidence: 99%